MOTIVASI BELAJAR SISWA KELAS XI MA PADA PEMBELAJARAN BIOLOGI SECARA DARING DI KECAMATAN KEBUMEN (STUDI ANALISIS) - Muliana, Diyanah; Hidayatullah, Ahmad Fauzan; Anggis, Eka Vasia (BIO-EDU: Jurnal Pendidikan Biologi, 2022)
This study aims to analyze the learning motivation of class XI MA students in online biology learning in Kebumen District. This research is qualitative and quantitative research methods (mixed method). The research was conducted in public and private MA in Kebumen District. The data analysis technique was carried out by calculating the percentage of students' answers based on indicators. The results showed that: (1) students' learning motivation of MA Negeri 1 Kebumen was high with an average of 69.3%; (2) the learning motivation of students at MA Negeri 2 Kebumen is moderate with an average of 66.6%; (3) the learning motivation of the students of MA Salafiyah Wonoyoso is high with an average of 71.1%; (4) the learning motivation of MA-PK Ma'arif 1 Kebumen students is high with an average of 71.5%. The learning motivation of class XI MA students in Kebumen District is categorized as high with an average of 69.6%. This is motivated by encouragement from within students and support from people around students so that students have a high desire to succeed even though there are still students who have moderate motivation even low.